2017
DOI: 10.18632/oncotarget.17685
|View full text |Cite
|
Sign up to set email alerts
|

Correction: LGR5 regulates pro-survival MEK/ERK and proliferative Wnt/β-catenin signalling in neuroblastoma

Abstract: Figure 5:LGR5 regulates MEK/ERK and Akt signalling. Immunoblotting demonstrating A. decreases in p-ERK1/2 (T202/Y204) and p-MEK1/2 (S217/221), B. Elevated Bim-EL and C. altered Akt phosphorylation and Rictor levels accompanying LGR5 knockdown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Reports have shown that the CSC marker, EpCAM, may be successfully used as a tumor marker in gastric, ovarian, and breast cancer because its high expression in these cancers is closely related to tumor growth, metastasis and advanced tumor stage (30)(31)(32). Similarly, increased expression of LGR5 in esophageal cancer and neuroblastoma can enhance tumor cell invasion and migration (33,34). Moreover, studies are underway to determine the relationship between LGR5 and PTC (35).…”
Section: Discussionmentioning
confidence: 99%
“…Reports have shown that the CSC marker, EpCAM, may be successfully used as a tumor marker in gastric, ovarian, and breast cancer because its high expression in these cancers is closely related to tumor growth, metastasis and advanced tumor stage (30)(31)(32). Similarly, increased expression of LGR5 in esophageal cancer and neuroblastoma can enhance tumor cell invasion and migration (33,34). Moreover, studies are underway to determine the relationship between LGR5 and PTC (35).…”
Section: Discussionmentioning
confidence: 99%
“…These tumor-spheres exhibited high expression of Wnt target genes and higher in vivo tumorigenicity (Coulon et al, 2011). Moreover, Vieira et al (2017) demonstrated the important role of LRG5 in regulating NB survival and proliferation via the MEK/ERK-Wnt/β-Catenin signaling pathways. In fact, MEK/ERK activity has been implicated in the maintenance of embryonic stem cells in the undifferentiated state as well as CSCs in glioma (Kwon et al, 2017), breast cancer (Baker et al, 2018), thyroid cancer (Wang K. et al, 2018), lung cancer (Ning et al, 2018), gastric cancer (Ning et al, 2018), glioblastoma (Wang F. et al, 2018) and rhabdomyosarcoma (Ciccarelli et al, 2016).…”
Section: Neuroblastoma Cancer Stem Cells: From Genes To Therapiesmentioning
confidence: 99%
“…This stem cell marker was found to be overexpressed in several types of cancers, such as glioblastoma (Nakata et al, 2013), cervical (Cao et al, 2017), breast (Yang et al, 2015) and colorectal cancers (Hirsch et al, 2014; Yanai et al, 2017). In addition, LGR5 was found to be overexpressed in high grade NB (Forgham et al, 2015; Vieira et al, 2017), working upstream of the MEK/ERK and Akt pro-survival signaling pathways (Vieira et al, 2017) which are often triggered in primary NB tumors (Opel et al, 2007).…”
Section: Bmi1mentioning
confidence: 99%
“…For instance, deletion of APC in LGR5-positive cells was related to the development of intestinal adenomas ( 5 ). LGR5 has also been shown to be diffusely overexpressed in colonic adenomas and adenocarcinomas and a range of other gastrointestinal and nongastrointestinal malignancies ( 10 16 ). These data raise the additional possibility that LGR5 expression in Barrett's epithelium may help predict progression to advanced neoplasia.…”
Section: Introductionmentioning
confidence: 99%